Choice biases in no-sample and delay testing in pigeons (Columba livia) - Pinto, Carlos (2021)
In experimental tasks that involve stimuli that vary along a quantitative continuum, some choice biases are commonly found. Take, for instance, a matching-to-sample task where animals must, following the presentation of sample stimuli (that differ in duration), choose between two or more comparison stimuli. In tests where no sample is presented there is usually a bias towards the comparison that is correct following the shortest sample. To examine some aspects of these choice biases, pigeons were trained in a symbolic matching-to-sample task with two durations of keylight as samples, where key pecking had to be maintained during sample presentation. Firstly, even though animals were required to attend to the sample, a preference for the "short" comparison in no-sample testing was found. This result disproves an account where this effect was hypothesized to happen due to non-programmed learning resulting from the animals failing to attend to some trials. Secondly, even though a bias for "short" was found in both no-sample and delay testing, the extent of the biases differed between tasks, thus suggesting that forgetting the sample presented during a delay does not necessarily land the animal in a state similar to presenting no sample at all to begin with.